TRACE FOSSILS AND BIOFABRICS AT THE PRECAMBRIAN-CAMBRIAN BOUNDARY INTERVAL IN WESTERN MONGOLIA - Goldring R.; Jensen S. (My University, 1996)
A small suite of trace fossils from the Zavkhan Basin (Govi-Altay) includes many of the ichnotaxa typical of the Nemakit-Daldynian, Tommotian and younger Cambrian stages, and other indeterminate forms. The traces are almost entirely from the sandstone intervals of the large-scale alternations of carbonate and siliciclastic sediments, thus emphasizing the facies and taphonomic controls on trace fossil distribution, and hence the inherent difficulties in using trace fossils in detailed global correlation, especially in using first appearances. The assemblage of traces and biofabrics is seen as resulting from the partly non-uniformitarian (non-actualistic) sedimentary environments that pertained over the boundary interval, rather than as evolutionary failures and subsequently vacated environments.
Keywords: Cambrian; Precambrian; Докембрий; Precambrian; Paleozoic::Cambrian; Палеозой::Кембрийская